HIV-Related Discrimination Reported by People Living with HIV in Lagos (Journal of Medicine, 2010)
Objective: Numerous factors have unilaterally and synergistically undermined the success of HIV and AIDS. It is in the light of the foregoing that this study was undertaken to evaluate some discriminatory experiences of people living with HIV and AIDS. Materials and Methods: This was a descriptive cross-sectional study on people with HIV and AIDS attending an outpatient clinic at Lagos State University Teaching Hospital within a period of 12 weeks. Respondents were recruited consecutively and data was collected with a semi-structured questionnaire. Response rate was 97.7%, analysis was done with Epi-info 6 statistical software. Results: Approximately one-fifth (17%) of respondents reported discrimination. Exploration on sources of discrimination showed that people discriminated against mentioned family members as being responsible in 49.1% of cases, 23.6% of respondents reported workplace discrimination and only 3.5% mentioned discrimination experienced by the Government workers. Conclusion: It is evident that success achieved so far in the fight against HIV and AIDS can easily be eroded if issues of discrimination against people living with HIV and AIDS are not addressed. Various innovative educational strategies targeting all stakeholders may be required if the battle against the spread of the virus must be won. Keywords: Discrimination, PLWHA, HIV, AIDS DOI:10.3329/jom.v11i1.4267 J Medicine 2010: 11: 39-41